Management theory and practice - Haslinda Abdullah (Penerbit Universiti Pertahanan Nasional Malaysia, 2017)
This book is a valuable resource for undergraduate students and professionals - and anyone whose aim is to gain understanding and knowledge on theories and practice in management. This book offers a clear and interesting introduction to management, covering the key context of management in a readable and user-friendly text.